Specific Features of Building Business-Processes Controlling Systems in Conditions of Economy Digitalization - E. A. Matushevskaya; O. S. Dotsenko (Вестник Российского экономического университета имени Г. В. Плеханова)
The article provides the research results, whose goal is to study problems of business-process controlling and to design methodological approaches and recommendations on practical realization of complex management of business-processes by using digital technologies at enterprises of service sector. The authors show and substantiate in theory business-processes at enterprises providing hairdressing services. A new vision of managing businessprocesses in current conditions of business is shown. Key principles and criteria of business-process optimization are identified, recommendations on resolving problems of using digital technologies are provided, which are necessary to optimize business-processes at the enterprise and on practical realization of complex management of businessprocesses at enterprises by using digital technologies, such as chat-bots and OCR/ICR systems meant for optical recognition and digitalization of enterprise work. The article shows that the use of modern digital technologies provides endless possibilities for business-process improvement by special systems that can change and enhance them continuously. It can simplify management methods, cut the cost of process optimization. The authors propose to introduce the system of business-process controlling and recommend to use indicators of enterprise work efficiency in view of separate processes.